Exposure of hazardous compounds in Furniture Painting Induces Oxidative Stress through Increasing Plasma Malondialdehyde (MDA) Levels - Oktaviani, Ratna; Jusup, Sinu Andhi; Indarto, Dono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Some heavy metals and organic solvents like toluene and formaldehydeare hazardous chemicals that are usually used to paint furniture.These compounds may increase oxidative stress andassociatewithseveraldiseases.Oxidative stress is characterized by high levels of free radicals, which induce macromolecule oxidation including lipid. Lipid is oxidized to become reactive and toxic compounds like ethane and MDA. This study aimed to investigatethedifferences ofplasma MDA levels between furniture painters and non-painters. Method:This study was analytical observationwithcross sectional research design. Thisstudywas conducted in several furniture industries in Taunan, Jepara. 14 people who work as furniture painters were classified as the painter group and 14 people who work as non-furniture painters become the control group. The plasma MDA levels were measured by using Thiobarbituric Acid ReactiveSubstances(TBARS) test. The collected data was statistically analyzed by using student t and multiple linear regression tests. Result:The majority of people in painter group aged between 20-34 years old and was younger than that of control group (25-39 years old). A significant increase in MDA levels was observed in the painter group, compared with MDA levels of the control group (5.74 ±0.39 vs. 1.94 ±0.33 µmol/L) with p value <0.001. Paint exposure was significantly associated with plasma MDA levels (r = 0,968; = 96,80%; p<0,001).Other factors such as nutritional status, food, psychic, sports and air pollutants had small proportion (3.20%) to increase the MDA levels. Conclusion:Plasma MDA levels of furniture painters increased approximately three-fold and are positively related to paint chemical exposure. This data suggests the possibility of oxidative stressin furniture painters although its pathogenesis needs further investigation. Keywords: Furniture painters,oxidativestress, plasma MDA level